PENGARUH MOTIVASI HIRARKI KEBUTUHAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. PELABUHAN INDONESIA III (PERSERO) CABANG TANJUNG EMAS SEMARANG - Ivanovich Perdana Kusuma; VS Tripriyo PS; Iwan - Hermawan (Admisi dan Bisnis, 2016)
PT Pelabuhan Indonesia III branch TanjungEmas Semarang, is a company engaging inproviding the harbour service which alwaysprovides satisfaction to the stakeholders. So itisimportant for the company to motivateemployees to work to achieve jobs satisfactionso thatemployees can improve theirperformance. The purpose of this researchwere, first, to findout the influencehierarchical motivation of needs onemployees jobs satisfaction, secondly,toreplicate the research that has been there , toproving empirically whether thereareinfluence hierarchical motivation of needson employees jobs satisfaction ,third,toprovingempirically whether there areinfluence between level of lateness on jobssatisfaction. Theresearch sample were 60employees of PT. Pelabuhan Indonesiabranch Tanjung emasSemarang asrespondents. The independent variable of thisresearch was hierarchicalmotivation of needsand the dependent variable was jobssatisfaction of employees . Themethod ofanalysis in this research used multiple linearregression test, t test,and f test .Whilethemethod of collecting data were questionnaireand literature study. The result oftheregression analysis shows that positivecoefficient, which meant that hierarchicalmotivationof needs gave positive andsignificant effect on jobs satisfaction based onthe result partiallyand simultaneously. Andthis result can be concluded that this researchempirically has been proved and in line withkusnul prianto research.